Teaching writing with the integration of grammar (subject-verb agreement) instruction to help pupils to write: an experimental study of ten year 4B pupils of Sekolah Kebangsaan Telagus/Jerok, Simunjan, Sarawak / Eddie Mandang - Mandang, Eddie (2004)
The purpose of this experimental study is to find out if there are improvements among the ten Year 4B pupils of SK. Telagus/Jerok, Simunjan after integrating grammar instruction. The teaching of grammar instruction(subject-verb agreement) can improve some of these pupils' writing. Somehow, little is known as to how to integrate grammar instruction in the writing process. Many researchers have made studies in many parts of the world and found that the teaching of writing with the integration of grammar workable as the integration of grammar instruction were done for longer duration. But for my case, it is just done or conducted within three weeks only and it is quite difficult for the pupils in the experimental group to achieve satisfactory results. However, this study seeks to find out the extent to which the integration of grammar instruction in the writing process helps improve pupils' writing. There are several strategies and techniques of integration carried out to help pupils improve their writing. Towards the end of the study, the pupils are interviewed to find out their opinions about the teaching of grammar. Recommendations for teachers and further research are also discussed.